A quick and easy access to a series of thiocyanated enaminones and 2‐iminothiazolones using PIDA under mild conditions. (25th April 2022) - Matsui, Daiki; Tanimori, Shinji
Abstract: A series of thiocyanated enaminones and 2‐iminothiazolones have been synthesized using PIDA as an oxidant with Brønsted acid under the mild reaction conditions starting from the acyclic and cyclic enaminones. Direct synthesis of 2‐iminothiazolones have also been achieved by treating alkali solution after thiocyanation in a one‐pot manner. Abstract : A series of thiocyanated enaminones and 2‐iminothiazolones have been synthesized using PIDA as an oxidant with Brønsted acid under the mild reaction conditions starting from the acyclic and cyclic enaminones.